(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2025)
The new educational standards for English at secondary level introduce a new area of foreign language-specific digital competence.Thus, pre-service teachers should be prepared for the development of lesson planning competences through the use of artificial intelligence and digital platforms as “conversation partners” as early as their first professionalization phase.